How many university students perceive themselves to be overweight/obese and how many have eating disorders during remote education due to COVID-19? A cross-sectional study - Goicochea Palomino, Anabela Eliane (2023)
Background: The COVID-19 pandemic caused a health crisis worldwide that ended up affecting the daily lives of university students. Considering prevention strategies for contagion and decreased physical activity, altered perceptions of body image were seen that may negatively disrupt their eating habits. Methods: Our cross-sectional survey-based study (N=180) had the objective to determine the association between body image perception and the risk of eating disorders in university students during the pandemic. We surveyed male and female university students aged 18-35 years using the Montero Anatomical Models questionnaire and the Eating Attitude Test-26 (EAT-26) as instruments. Results: Most of the university students were female (67.8%) with an average age of 22.8±3.9 years. 51.1% perceived themselves as overweight and 53.9% were at low risk of an eating disorder. This mainly affected women (47.5%), the 21-30 age group (43.2%), and those who perceived themselves as underweight (58.9%) or obese (50%). Likewise, we found differences in body image perception between genders (p=0.009), and no association was found between body image and eating disorders (p=0.661). Conclusion: Even though most university students perceived themselves as overweight, they had a low risk of an eating disorder. Considering the influence that body image perception has on their lifestyle, it is necessary to promote healthy eating habits and self-esteem strategies to prevent the appearance of eating disorders due to body dissatisfaction in the context of the “new normal”.